A Study on the Participatory Forestry Land Use and Farming Practices in the Chittagong Hill Tracts. Bangladesh - Chowdhury, Abdullah Al Mamun; Khan, Niaz Ahmed; Serajul Haq, S. M. (Indian Forester, 2020)
The study explored the genesis and current status and forms of land use and farming practices in Chittagong hill tracts region of Bangladesh. Some major observations include the following: (i) Lands allotted for horticulture and agriculture were converted to forestry, agro-forestry and agriculture by the participants of the government and NGO projects. Livestock rearing was found as a common practice, (ii) Forestry was preferred topographically as a suitable land use in the region. Both the government and NGO participants were found to be practicing some form of pure forestry, particularly in the comparatively steep slopes. (Hi) Agroforestry, by combining long gestation forestry with short-term horticultural and agricultural species, was found to be the dominant land use practice in CHT. (iv) Agriculture was found as a general land use practice in CHT, mainly following the traditional system (v) Inter-sectoral coordination among the PF agencies and necessary service provision by GO and NGO agencies were almost absent. Strong linkages through inter-sectoral coordination for both GO and NGO agencies must be undertaken in order to involve related agencies in land-based development interventions.